Modelling and simulation of sprinters' health promotion strategy based on sports biomechanics. Issue 4 (2nd October 2021) - Huifeng, Wang; Shankar, Achyut; Vivekananda, G.N.
Abstract : With the rapid development of the new edge discipline sports biomechanics, modelling and simulation of human motion as one of the cutting-edge research topics in sports biomechanics is receiving more and more attention. Based on the establishment of the three-dimensional simulation system model of human knee joint and the analysis of buckling motion, this paper uses the three-dimensional image registration knee joint motion analysis method to carry out the research on knee flexion movement to solve the knee joint injury problem of sprinters. The results showed that medial collateral ligament injury and meniscus injury were more common in all types of knee joint injuries, accounting for 24% respectively 7% and 22.4%. The incidence of lateral collateral ligament injury was relatively small, accounting for only 5.6%. And the research shows that the foot strength curve recognition method based on biomechanics sprinters knee joint simulation model is an advanced and complete strategy to reduce sprinters knee joint injury, and it can achieve better results in sprinters knee joint nursing.